Homo Deus: A brief history of tomorrow - Harari, Yuval Noah (London Penguin Random House, 2017)
**THE MILLION COPY BESTSELLER**Sapiens showed us where we came from. In our increasingly uncertain times, Homo Deus shows us where we're going.'Spellbinding' GuardianThe world-renowned historian and intellectual Yuval Noah Harari envisions a near future in which we face a new set of challenges. Homo Deus explores the projects, dreams and nightmares that will shape the twenty-first century and beyond - from overcoming death to creating artificial life.It asks the fundamental questions: how can we protect this fragile world from our own destructive power? And what does our future hold?'Even more readable, even more important, than his excellent Sapiens' Kazuo Ishiguro'Homo Deus will shock you. It will entertain you. It will make you think in ways you had not thought before' Daniel Kahneman, bestselling author of Thinking, Fast and Slow
Keywords: World History